Research progress on brewing technology and flavor of Fuyu-flavor Baijiu - CHEN Yichao, MAO Jian, ZHOU Zhilei, CHEN Songqiang, WANG Weimin (Zhongguo niangzao)
Fuyu-flavor Baijiu is one of the representative varieties of Chinese Baijiu, which has the unique characteristics combination of strong flavor, light flavor and sauce flavor. With the development of detection technology, microbiomics and molecular sensory science, the understanding of Fuyu- flavor Baijiu has gradually deepened. In this paper, the research on brewing process, main brewing microbial species (environment, Jiuqu and fermentation process), typical flavor wheel and composition ratio relationship in recent years were summarized, and research and development trend of Fuyu-flavor Baijiu were prospected, aiming to provide reference for further revealing the complex flavor formation mechanism.